Serpent gate eaudiobook Kevin kerney mysteries series, book 3. - McGarrity, Michael (Kevin Kerney, 2012)
In this complex tale of greed and revenge, best-selling author Michael McGarrity shrewdly blends riveting action with magnificent southwestern scenery. Serpent Gate portrays former Santa Fe policeman Kevin Kerney in a perilous struggle against corrupt officers, New Mexico politicians, and a deadly enemy from the past. Recruited for the State police by the new chief, Kerney searches the mountainous countryside for a patrolman's killer. Quickly solving the months-old murder, he takes on a more challenging assignment: recover the priceless art collection stolen from the governor's office. As Kerney pursues the mastermind behind the theft, he finds himself returning to the violent roots of his first case. Michael McGarrity, a former police officer for Santa Fe County, draws on his own experience to create plots packed with nonstop excitement and believable predicaments. Narrator George Guidall's stellar performance will hold you spellbound from the intriguing opening to the surprise ending. For more gripping Kevin Kerney mysteries, don't miss: Tularosa and Mexican Hat.